Divide. Draw a quick picture. 143 divided by 11

Answers

Answer 1
Answer:

A 143 divided by 11 equals 13.

To calculate 143 divided by 11 using long division, follow these steps:

  • Place the dividend (143) inside the long division symbol, and write the divisor (11) outside the symbol.
  • Check how many times 11 can be divided into the first digits of the dividend (1). The result is 1 because 11 * 1 = 11, and this is the largest multiple of 11 that fits into 14 (the first two digits of 143).
  • Write the result (1) on top, above the 4 (the first digit of 143).
  • Multiply 11 by 1 (the quotient), which equals 11, and write the result under 14.
  • Subtract 11 from 14 (14 - 11 = 3).
  • Bring down the next digit (3) to form 33.
  • Check how many times 11 can be divided into 33. The result is 3 (11 * 3 = 33).
  • Write 3 on top, above the 3.
  • Multiply 11 by 3, which equals 33, and write the result under 33.
  • Subtract 33 from 33 (33 - 33 = 0).
  • As there's no remainder and all the digits have been brought down, the final result is 13. So, 143 divided by 11 equals 13.

To know more about divided:

brainly.com/question/15381501


#SPJ6

Answer 2
Answer: 143 divided by 11 equals 13

Related Questions

y 2; r t ’ r i n than STEELE thud 8. Draw an example of 3 shape that has at least one right angle my one angle less than a right angle and one angle greater than a right angle Label the angles
How many tenths equal to a one
Help I can’t figure it out
Find the rule the pattern is using 4,20,100,50
What are the answers to the questions? Picture Below.

Write an explicit formula for the sequence -3, 1, 5, 9 ... i think the answer is a_n=-3+4(n-1) i just need someone to double check me :)

Answers

Answer:

you are correct

Step-by-step explanation:

The sequence has a common difference between consecutive terms

d = 9 - 5 = 5 - 1 = 1 - (- 3) = 4

This indicates the sequence is arithmetic with explicit formula

a_(n) = a₁ + (n - 1)d

where a₁ is the first term and d the common difference

Here a₁ = - 3 and d = 4, thus

a_(n) = - 3 + 4(n - 1) = - 3 + 4n - 4 = 4n - 7

I need help solving equations with variables on both sides. Please help and show me the work!x+3= -x-5

Answers

x+3=-x+5\ \ \ \ | add\ x\ on\ both\ sides\n\n2x+3=5\ \ \ \ | subtract\ 3\n\n2x=-2\ \ \ | divide\ by\ 2\n\nx=-1

Answer:

x=-4

Step-by-step explanation:

x+3= -x-5\n+x -3=+x -3\n(2x)/(2) =(-8)/(2) \nx=-4 First you combine like terms then you simplify after that you have your answer.

Lisa's store collects 5% sales tax on every item sold. If she collected $22.00 in sales tax, what was the cost of the item her store sold?

Answers

5% of sold is tax
22.00=tax
therefor
22.00=5% of total

5%=5/100=1/20
'of' means multiply
22.00=1/20 times totl
multiply both sides by 20/1 to clear fraction
440.00=total



cost of items is $440.00
22/0.05 = 440
therefore the cost of the item was $440

(5% of 440 = 22)

A youth chorus has 30 members. There are 14 boys in the chorus. What is the ratio of boys to girls in simplest form?

A.7/15


B.8/15


C.7/8


D.8/7

Answers

so boys to girls=

14 boys
30-14=girls=16

boys to girls=14:16
treat it as a fraction
14/16
simplify
divide 2
7/8
that's simplest form
7/8 or C is the answer

Answer:

your answer would be c. 7/8

Step-by-step explanation:


Two students participated in a fund-raiser. Each sold a combination of pencils and notebooks. The first student sold 2 pencils and 8 notebooks for a total of $17. The second student sold 10 pencils and 3 notebooks for a total of $11. Find the price of each item.Write a system of equations (two equations), and define the variables also.
x=
y=
1)
2)
9 POINTS! Please help!

Answers

2x + 8y = 17
10x + 3y = 11

We need to solve the system of equations.

x = pencils
y = notebooks

If we solve by graphing, we get the answer:

One pencil costs 0.50 dollars
One notebook costs 2.00 dollars

What is the following sentence written as an expression?" Add the product of 3 and 6 to 4".

Answers

Answer:

The required expression is(3* 6)+4.

Step-by-step explanation:

Consider the provided sentence.

"Add the product of 3 and 6 to 4".

Product of 3 and 6 can be written as:

3* 6

Now we need to add this product to 4.

Thus the required expression for "Add the product of 3 and 6 to 4" is:

(3* 6)+4

Hence, the required expression is(3* 6)+4.

the expression will look like this. (3*6)+4